2006
DOI: 10.1002/hyp.6144
|View full text |Cite
|
Sign up to set email alerts
|

Multiple modes of storm runoff generation in a North Carolina coastal plain watershed

Abstract: Abstract:The results of field measurements conducted in a small (19Ð37 ha) agricultural watershed on the North Carolina coastal plain during the summer of 1996 are presented. The objective of the study was to develop a more complete understanding of basin response in the region with respect to stormflow generation and, in particular, to identify the processes that determine storm runoff and the conditions under which such processes occur. Twenty-four storm events were monitored, including two tropical storm sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 26 publications
(25 reference statements)
8
52
0
Order By: Relevance
“…At the small catchment, hydrological connectivity is influenced by the lateral preferential flow or rill induced by agricultural linear features, such as furrows, back furrows, ditches, and vehicle wheeling (Cerdan et al, 2004;Lesschen et al, 2009;Slattery et al, 2006). Specifically, water transfer from fields to catchment outlets is influenced by drainage ditch networks.…”
Section: S Han Et Al: Runoff Formation In Agricultural North Huaihementioning
confidence: 99%
“…At the small catchment, hydrological connectivity is influenced by the lateral preferential flow or rill induced by agricultural linear features, such as furrows, back furrows, ditches, and vehicle wheeling (Cerdan et al, 2004;Lesschen et al, 2009;Slattery et al, 2006). Specifically, water transfer from fields to catchment outlets is influenced by drainage ditch networks.…”
Section: S Han Et Al: Runoff Formation In Agricultural North Huaihementioning
confidence: 99%
“…Water fluxes between slopes and wetlands are generally small (Devito et al, 2005a;Branfireun and Roulet, 1998), and hillslope-stream connectivity is rare (Redding and Devito, 2010;Ali et al, 2011). These features in lowland forested watersheds appear to be controlled by the complex, and poorly understood, interplay of climate, soils, and geology (Devito et al, 1996(Devito et al, , 2005bSlattery et al, 2006;Sun et al, 2002). Furthermore, topography is not a clear driver of runoff generation (Buttle et al, 2004;Devito et al, 2005b) since vertical subsurface flow often dominates over lateral subsurface flow (Todd et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Storm runoff varies widely, from none to over 70 % of rainfall (Epps et al, 2013), which is believed to be related to soil water and depression storage. In low-gradient forested watersheds, we anticipate an even greater coupling of transpirative and soil water dynamics in runoff generation processes (Amatya et al, 1996;Slattery et al, 2006;Sun et al, 2010;Amatya and Skaggs, 2011;Dai et al, 2011;Skaggs et al, 2011;Tian et al, 2012). Using isotope effects of transpiration and evaporation from a global data set, Jasechko et al (2013) demonstrated that transpiration is the major component of the total evapotranspiration (ET) process in the global water cycle.…”
Section: Introductionmentioning
confidence: 99%